The role of Muslim women in generating household income through micro or small scale enterprises: the case study of Amanah Ikhtiar Malaysia - Duasa, Jarita; Md Saad, Norma (IIUM Press, 2011)
The study investigates whether the additional income obtained from micro-enterprises carried out by female members of Amanah Ikhtiar Malaysia (AIM) is able to increase the quality of life and socio-economic status of the member family. For this purpose, the study conducted a survey on respondents who are the participants of AIM program using convenience sampling in Perak and Kelantan. The analyses are done using descriptive statistics, tests of mean differences of dependent and independent samples, one way ANOVA and multiple regression of OLS method. The findings of the study show the success of AIM microfinance scheme to uplift the standard of living of poor households in Perak and Kelantan through the participation of female members who are majority Muslim women. The obvious differences between income level before and after they joined the scheme are tested and it is found that the differences are highly significant. This is highly supported by the ownership of vehicle(s) which is believed to assist them in conducting economic activities from the project and the experiences that they have through higher age. Majority of the respondents agree that the scheme enables them to provide more education for the children as well as the healthcare of family members. Besides, the scheme has enabled them to fulfill their duty as Muslim through zakah payments and even signifies their important role in increasing the standard of living of the family through small scale businesses/projects.